2023
DOI: 10.1038/s41467-023-37401-3
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxially grown silicon-based single-atom catalyst for visible-light-driven syngas production

Abstract: Improving the dispersion of active sites simultaneous with the efficient harvest of photons is a key priority for photocatalysis. Crystalline silicon is abundant on Earth and has a suitable bandgap. However, silicon-based photocatalysts combined with metal elements has proved challenging due to silicon’s rigid crystal structure and high formation energy. Here we report a solid-state chemistry that produces crystalline silicon with well-dispersed Co atoms. Isolated Co sites in silicon are obtained through the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…To explore the electronic properties, we carried out X-ray photoelectron spectroscopy (XPS) characterizations of Co/N–C-600, Co/N–C-800, and Co/N–C-1000. As shown in Co 2p XPS spectra, the content of metallic Co 0 increased from Co/N–C-600 to Co/N–C-800 and Co/N–C-1000 (Figure e). N 1s XPS spectra showed that the peaks at 399.4, 401.4, 400.2, and 398.8 eV were ascribed to Co–N, graphitic N, pyrrolic N, and pyridinic N, respectively , (Figure f).…”
mentioning
confidence: 73%
“…To explore the electronic properties, we carried out X-ray photoelectron spectroscopy (XPS) characterizations of Co/N–C-600, Co/N–C-800, and Co/N–C-1000. As shown in Co 2p XPS spectra, the content of metallic Co 0 increased from Co/N–C-600 to Co/N–C-800 and Co/N–C-1000 (Figure e). N 1s XPS spectra showed that the peaks at 399.4, 401.4, 400.2, and 398.8 eV were ascribed to Co–N, graphitic N, pyrrolic N, and pyridinic N, respectively , (Figure f).…”
mentioning
confidence: 73%
“…More recently, a silicon-based Co SAC was reported for the production of syngas with a highly tunable H/C ratio. 239 A solid-state epitaxy method was used for the construction of such a SAC with Co SAs well dispersed on crystalline silicon, through a multistep variable-temperature annealing including the preliminary incorporation of Co atoms in the Si lattice and the following decomposition of the CoSi 2 domain. With the addition of a particular photosensitizer and sacrificial agent, CO and H 2 yields of 4.7 mol g (Co) −1 and 4.4 mol g (Co) −1 were achieved through visible-light-driven CO 2 reduction, in which the H/C ratio could be tuned from 0.8 to 2 by modulating the Co loading amount.…”
Section: Single-atom Catalysis In Typical Co 2 Con...mentioning
confidence: 99%
“…TON (Equation ), which represents the maximum achievable turnover number in unit time, is a crucial parameter for evaluating the practicality of a catalyst in industrial applications TON = Number of reacted electrons per second Number of active sites in a photocatalyst …”
Section: Basic Principles and Challenges Of Photocatalytic Co2rrmentioning
confidence: 99%
“…In industrial applications, maintaining a stable CO/H 2 ratio is crucial as syngas with ratios of 1:1, 1:2, and 1:3 serves as raw materials for hydroformylation, methanol synthesis, and methanation reactions, respectively. , Therefore, achieving continuous syngas production at a consistent CO/H 2 ratio represents a key objective in developing photocatalytic syngas production units. Zhenyu Yang proposed that the in situ formation of metal silicide could facilitate silicon growth and enable the incorporation of dopant metals into the metal silicide/silicon interface. Consequently, cobalt silicide (CoSi 2 ) was employed as a template to promote the atomic epitaxy-based in situ growth of diamond-structured crystalline Si (c-Si), thereby incorporating Co atoms into the high-temperature domain of c-Si lattice during CoSi 2 decomposition.…”
Section: Photocatalytic Co2rr To Different Productsmentioning
confidence: 99%
See 1 more Smart Citation